Kurikulum Pendidikan Dasar di Indonesia: Tantangan, Inovasi, dan Implementasinya di Era Digital - Romi Laspita; Cindy Fatika Sari; Hanifa Dzakiyya; Rifdah Afifah; Siti Rahma Mailani; Nurkauliah Aisyah; Rina Nurul Aisyah; Said Aziz; Azrah Syarifah Kamilla; Nadia Fahira Anggraini; Ratih Nurjannah Pohan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Basic education curriculum in Indonesia is undergoing a strategic transition through the institutionalization of the Merdeka Curriculum and the expansion of digital learning ecosystems. This article aims to analyze the main challenges, innovations, and implementation strategies of Indonesia’s basic education curriculum in the digital era. The study used a narrative literature review by synthesizing policy documents, national statistics, international assessment reports, and recent scholarly publications published mainly within the last ten years. The findings indicate that curriculum reform is driven by three urgent needs: strengthening foundational literacy and numeracy, improving teacher capacity for differentiated and project-based learning, and reducing digital inequality among schools and regions. The Merdeka Curriculum provides innovation through competency-based learning outcomes, flexible teaching modules, diagnostic assessment, and the Pancasila Student Profile Strengthening Project. However, implementation remains uneven because teacher readiness, school infrastructure, digital access, and data-based school management differ significantly across contexts. Digital technology can support personalization, collaboration, and multimodal learning, but it must be used pedagogically, ethically, and inclusively. The article concludes that curriculum implementation in basic education should prioritize teacher professional development, equitable digital infrastructure, contextual school curriculum development, and continuous evaluation based on learning outcomes rather than administrative compliance.